If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -1(5x + 6) = 18 Reorder the terms: 3x + -1(6 + 5x) = 18 3x + (6 * -1 + 5x * -1) = 18 3x + (-6 + -5x) = 18 Reorder the terms: -6 + 3x + -5x = 18 Combine like terms: 3x + -5x = -2x -6 + -2x = 18 Solving -6 + -2x = 18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -2x = 18 + 6 Combine like terms: -6 + 6 = 0 0 + -2x = 18 + 6 -2x = 18 + 6 Combine like terms: 18 + 6 = 24 -2x = 24 Divide each side by '-2'. x = -12 Simplifying x = -12
| 40x+-2=8 | | 179=-3x+7(-3x+5) | | 3-4(2-5x)=51 | | 80x^2+68x+12= | | (256x^12y^16)^1/4 | | 3j+34=12 | | g-3.75=49.75 | | 10x-3(2x+5)=13 | | 58p/4=20 | | 55=-7v+6 | | -123x+16-27x+297=19x-(74+120) | | 62.9296(1.009795073-1.031752943y)+64.9278y=63.546 | | 2x+4-2.8=4.5 | | b/2-7=-17 | | 5-(3x+2)=-2 | | 40x-2=8 | | -19-6(c-8)=35 | | 25=3x+15 | | 7x-(5x+6)=7X-26 | | -126=-9-9n | | 0.07(4x-2)=0.28(x-2)+0.42 | | (19y+8)-(7y+10)=22 | | 5(-6-4.5)=3(8+10.5) | | 4+m-3=196 | | c+1/8=0/4 | | 5x+21/8=x/4 | | 2y-3+y=y-5-6 | | 3(-2+12)=8-2(n-8) | | x+0.05=36750 | | -2(6-10n)=10(2-6) | | 0.9x-2.2=3.5x+1.7 | | -5-8(1-x)=2(7x-6) |